A STUDY OF THE CULTURAL AMBIANCE DELINEATED IN SUNITI NAMJOSHI’S SELECT POEMS IN THE LIGHT OF HER MEDITATIVE SENSIBILITY WHICH IS GIFTED WITH IRONIC PERCEPTION - Arul Jayraj, S. Joseph (Advances in Social Sciences Research Journal, 2015)
This paper takes into account the cultural ambiance against which Indian women poets have kept the feminine poetic tradition and poetic sensibility vibrant and considers Indian poetry in English by women as the daring assertion of the modern Indian woman. It analyses the cultural ambiance delineated in a few of the poet’s select poems in the light of her meditative sensibility which is gifted with ironic perception.